Mortality, survival and incidence rates in the ITALUNG randomised lung cancer screening trial - Paci, Eugenio; Puliti, Donella; Lopes Pegna, Andrea; Carrozzi, Laura; Picozzi, Giulia; Falaschi, Fabio; Pistelli, Francesco; Aquilini, Ferruccio; Ocello, Cristina; Zappa, Marco; Carozzi, Francesca M; Mascalchi, Mario (Thorax, 2017)
BackgroundITALUNG is contributing to the European evaluation of low-dose CT (LDCT) screening for lung cancer (LC).MethodsEligible subjects aged 55–69 years, smokers or ex-smokers (at least 20 pack-years in the last 10 years), were randomised to receive an annual invitation for LDCT screening for 4 years (active group) or to usual care (control group). All participants were followed up for vital status and cause of death (at the end of 2014) and LC incidence (at the end of 2013). Pathological and clinical information was collected from the Tuscan Cancer Registry data.Results1613 subjects were randomly assigned to the active group and 1593 to the control group. At the end of the follow-up period 67 LC cases were diagnosed in the active group and 71 in the control group (rate ratio (RR)=0.93; 95% CI 0.67 to 1.30). A greater proportion of stage I LC was observed in the active group (36% vs 11%, p<0.001). Non-significant reductions of 17% (RR=0.83; 95% CI 0.67 to 1.03) for overall mortality and 30% (RR=0.70; 95% CI 0.47 to 1.03) for LC-specific mortality were estimated.ConclusionsDespite the lack of statistical significance, the ITALUNG trial outcomes suggest that LDCT screening could reduce LC and overall mortality. Moreover, the comparison of the number of LC cases diagnosed in the two groups does not show overdiagnosis after an adequate follow-up period. A pooled analysis of all European screening trials is advocated to assess the benefit-to-harm ratio of LDCT screening and its implementation in public health settings.Trial registration numberResults, NCT02777996.